Pengaruh Penggunaan Financial Technology QRIS (Quick Response Code Indonesian Standard) Terhadap Tingkat Pendapatan Pedagang Kaki Lima di Sekitar Universitas Muhammadiyah Surakarta - Fania Maulida Pangesti; Annisa Fitrotun Nadhiroh; Erni Ghuri; Dewi Sekar Tanjung; Dyah Ayu Kusumaningrum; Dira Rosyida Noor Adiba (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Quick Response Code Indonesian Standard or QRIS is a QR code network used by various Payment System Service Providers (PSSP). Most street vendors have implemented this payment method. For various reasons, one of which is to increase the amount of income because it is believed that the convenience provided by QRIS will be directly proportional to the income level of Street Vendors around the Muhammadiyah University of Surakarta. This research uses primary data and secondary data. Primary data was taken from a sample of street vendors around Muhammadiyah University, Surakarta. The sample was determined based on criteria determined by the researcher, namely 8 respondents. Meanwhile, secondary data was taken from journals and articles. The research method used is a descriptive qualitative method using in-depth interviews and data analysis using content analysis methods. Keyword: QRIS, Payment Methods and Street Vendors